Prevalence of Frailty Among Patients Undergoing Elective Surgery in Tertiary Care Hospital - Khan, Rao Noman; Sharafat, Muhammad Azhar; Aqeel, Muhammad Nauman; Azam, Jehanzaib Muhammad; Aftab, Sadqa (Biological and Clinical Sciences Research Journal, 2025)
Frailty is an emerging perioperative risk factor associated with adverse postoperativeoutcomes, particularly in the elderly population. Despite global interest in frailty assessment, limited data exist from low-middle income countries like Pakistan regarding the prevalence of frailty and its implications in surgical outcomes. Objective: The aim of the present study was to identify the frequency of frail patient among elderly population admitted for orthopedic and vascular surgeries and to compare outcome of with and without frail patient admitted for orthopedic and vascular surgery. Methods: This crossectional study was conducted at Department of Anaesthesiology, Shaheed Mohtarma Benazir Bhutto Institute of Trauma, Karachi, from 30/NOV/2024 till 31/MAR/2025. All consecutive adults (≥ 18 y) 72 patients scheduled for vascular and orthopaedic surgery were screened at the pre-operative assessment clinic. Emergency Caesarean sections, day-case procedures lasting < 30 min, and patients unable to consent or complete frailty testing (e.g., severe cognitive impairment without a proxy) were excluded. Results: Among the 72 patients analysed (34 frail, 38 non-frail), the two groups were practically identical in age (74.3 ± 1.1 vs 74.6 ± 1.0 years; p = 0.84) and operative profile. Mean total FRAIL scores were low in both cohorts (1.0 ± 0.16 for frail patients and 0.87 ± 0.11 for non-frail; p = 0.61). Surgical duration averaged roughly 2 h (138.5 ± 8.3 min vs 145.2 ± 8.1 min; p = 0.56) with comparable estimated blood loss (474 ± 52 ml vs 510 ± 49 ml; p = 0.61) and crystalloid administration (1.72 ± 0.14 L vs 1.77 ± 0.13 L; p = 0.83). Post-operative ward stay was just over three days in both groups (3.44 ± 0.53 vs 3.11 ± 0.55 days; p = 0.66), while median stays in HDU and ICU remained short and statistically indistinguishable. Conclusion: In this study, mild frailty did not independently worsen early peri-operative outcomes when patients were managed within structured optimisation pathways.